Pengaruh Self Efficacy, Emotional Intelligent Terhadap Turnover Intention yang Dimediasi Work Engagement Pada Gen Z di Perusahaan Startup Jakarta Selatan dan Jakarta Pusat - Febyana, Nadhira Salsa; Emilisa, Netania; Ramadini, Salwa Salsabila; Prayogi, Raihan (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to better understand how the practice of Self Efficacy, Emotional Intelligence, is related to Turnover Intention mediated by Work Engagement, analysis needs to be carried out to explain the underlying psychological mechanisms which will later help explain the relationship between Self Efficacy, Emotional Intelligence, and mediated Turnover Intention by Work Engagement. This research design was carried out by means of hypothesis testing which was used to test the influence of Self Efficacy, Emotional Intelligence on Turnover Intention mediated by Work Engagement in Genz in Startup Companies. Based on the research results, Self Efficacy descriptive statistics show that Generation Z workers agree with the existence of Self Efficacy in Startup companies in South Jakarta and Central Jakarta. The results of hypothesis testing show that there is a significant positive influence between Self Efficacy and Work Engagement. The results of hypothesis testing show that there is a significant positive influence between Emotional Intelligence and Work Engagement. The results of hypothesis testing show that there is no significant negative influence between Self Efficacy and Turnover Intention. The results of hypothesis testing show that there is no significant negative influence between Emotional Intelligence and Turnover Intention. The results of hypothesis testing show that there is a significant negative influence between Work Engagement and Turnover Intention. The results of hypothesis testing show that there is a significant negative influence between Self Efficacy on Turnover Intention mediated by Work Engagement. The results of hypothesis testing show that there is a significant negative influence between Emotional Intelligence on Turnover Intention mediated by Work Engagement.